Blended learning factors influencing student engagement in higher education - Lai Thi Thu Thuy; Nguyen Thu Hoai (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examines the factors associated with student engagement (SE) in blended learning environments in higher education, with particular attention to the mediating role of perceived usefulness (PU). Drawing on the information systems success model and the technology acceptance model (TAM), an integrated research model incorporating system quality (SQ), content quality (CQ), teacher support (TS), interaction (IN), PU, and SE was proposed and empirically tested. Data were collected from 288 undergraduate students at universities in Vietnam and analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that SQ, CQ, TS, and IN are significantly associated with PU. PU, in turn, shows a strong positive association with SE. While SQ and TS are also directly related to engagement, the relationships between CQ, IN, and SE are primarily indirect through PU, highlighting its central mediating role. These findings contribute to a more nuanced understanding of how blended learning factors jointly explain SE and offer theoretical and practical insights for the design and implementation of blended learning in higher education.